Content Classes Delivered in English at a Private School in Medellín– A Case Study - Blandón, Rubén Darío Cano (IJRDO- Journal of Educational Research, 2017)
This thesis examines the implementation of geography and history classes delivered in English in a private school in Medellin-Colombia from three perspectives: the teachers’ profile, their methodology, and the use of materials in light of Content-Based Instruction (CBI). The data was collected through surveys, class observations, and interviews. The results indicate that the content teachers lack training in teaching their classes through the medium of English; that there is no integration of content and language teaching, and that there is absence of collaborative work between the language teachers and the content teachers. This research also concludes that it is fundamental to revisit the concepts of bilingualism and bilingual education in the Colombian context.